Relevansi hukum positif dengan hukum islam pada tindak pidana pembunuhan di negara Indonesia - Haqqy, Ahmad Jauhari; Putri, Anggun Wahyu; Nur ‘Aini, Maslikhah Desi (Maliki Interdisciplinary Journal, 2025)
Legal injustice in Indonesia, especially in cases of murder, gives the impression that the law favors those in power. This study aims to compare the criminal law system in Indonesia with the principles of justice in Islamic law, especially fiqh jinayah. By conducting a literature review, this study analyzes the inequality in law enforcement and its impact on public trust. The case study of Ferdy Sambo is the main focus to show how power can influence the legal process. The findings show that although positive law has provided sanctions, true justice has not yet been fully achieved. Therefore, this study recommends the need for synergy between the principles of justice in Islamic law and positive law to create a more just and moral justice system.